The Effects of Balloon Occlusion of the Aorta on Cerebral Blood Flow, Intracranial Pressure, and Brain Tissue Oxygen Tension in a Rodent Model of Penetrating Ballistic-Like Brain Injury - Bailey, Zachary S.; Cardiff, Katherine; Yang, Xiaofang; Gilsdorf, Janice; Shear, Deborah; Rasmussen, Todd E.; Leung, Lai Yee (Frontiers in Neurology, 2019)
Trauma is among the leading causes of death in the United States. Technological advancements have led to the development of resuscitative endovascular balloon occlusion of the aorta (REBOA) which offers a pre-hospital option to non-compressible hemorrhage control. Due to the prevalence of concomitant traumatic brain injury (TBI), an understanding of the effects of REBOA on cerebral physiology is critical. To further this understanding, we employed a rat model of penetrating ballistic-like brain injury (PBBI). PBBI produced an injury pattern within the right frontal cortex and striatum that replicates the pathology from a penetrating ballistic round. Aortic occlusion was initiated 30 minutes post-PBBI and maintained continuously (cAO) or intermittently (iAO) for 30 minutes. Continuous measurements of mean arterial pressure (MAP), intracranial pressure (ICP), cerebral blood flow (CBF), and brain tissue oxygen tension (PbtO2) were recorded during, and for 60 minutes following occlusion. PBBI increased ICP and decreased CBF and PbtO2. The arterial balloon catheter effectively occluded the descending aorta which augmented MAP in the carotid artery. Despite this, CBF levels were not changed by aortic occlusion. iAO caused sustained adverse effects to ICP and PbtO2 while cAO demonstrated no adverse effects on either. Temporary increases in PbtO2 were observed during occlusion, along with restoration of sham levels of ICP for the remainder of the recordings. These results suggest that iAO may lead to prolonged cerebral hypertension following PBBI. Following cAO, ICP and PbtO2 levels were temporarily improved. This information warrants further investigation using TBI-polytrauma model and provides foundational knowledge surrounding the non-hemorrhage applications of REBOA including neurogenic shock and stroke.